Anatomic variation of cranial parasympathetic ganglia - Selma Siéssere; Mathias Vitti; Luiz Gustavo de Sousa; Marisa Semprini; Mamie Mizusaki Iyomasa; Simone Cecílio Hallak Regalo (Sociedade Brasileira de Pesquisa Odontológica, 2008)
Having broad knowledge of anatomy is essential for practicing dentistry. Certain anatomical structures call for detailed studies due to their anatomical and functional importance. Nevertheless, some structures are difficult to visualize and identify due to their small volume and complicated access. Such is the case of the parasympathetic ganglia located in the cranial part of the autonomic nervous system, which include: the ciliary ganglion (located deeply in the orbit, laterally to the optic nerve), the pterygopalatine ganglion (located in the pterygopalatine fossa), the submandibular ganglion (located laterally to the hyoglossus muscle, below the lingual nerve), and the otic ganglion (located medially to the mandibular nerve, right beneath the oval foramen). The aim of this study was to present these structures in dissected anatomic specimens and perform a comparative analysis regarding location and morphology. The proximity of the ganglia and associated nerves were also analyzed, as well as the number and volume of fibers connected to them. Human heads were dissected by planes, partially removing the adjacent structures to the point we could reach the parasympathetic ganglia. With this study, we concluded that there was no significant variation regarding the location of the studied ganglia. Morphologically, our observations concur with previous classical descriptions of the parasympathetic ganglia, but we observed variations regarding the proximity of the otic ganglion to the mandibular nerve. We also observed that there were variations regarding the number and volume of fiber bundles connected to the submandibular, otic, and pterygopalatine ganglia.